Anti-colon Cancer Effects of Dendrobium officinale Kimura & Migo Revealed by Network Pharmacology Integrated With Molecular Docking and Metabolomics Studies - Tao, Shengchang; Li, Jinyan; Wang, Huan; Ding, Shaobo; Han, Weichao; He, Ruirong; Ren, Zhiyao; Wei, Gang (Frontiers in Medicine, 2022)
Objective: The present study aimed to investigate the potential mechanism of the D. officinale on CRC and the relevant targets in the pathway using a network pharmacological approach. Methods: 1) We identified the major bioactive components of D. officinale by UPLC-ESI-MS/MS and established the in-house library. 2) Target prediction were performed by the SwissADME and the Swiss Target Prediction. 3) A protein–protein interaction (PPI) network and Ingredients–Target-Pathway network (I-T-P network) were constructed. 4) GO pathways and KEGG pathways enrichment analysis were carried out by the Metascape database. 5) Molecular docking was performed by AutoDock software. 6) A series of experimental assays including cell proliferation, cell invasion and migration, TUNEL staining, and cell apoptosis in CRC were performed in CRC cell lines, HT-29, Lovo, SW-620 and HCT-116, to confirm the inhibitory effects of D. officinale. Results: 1) 396 candidate ingredients of D. officinale were identified by UPLC-ESI-MS/MS and selected from database. 2)1666 gene symbols related to CRC were gathered from OMIM, GeneCards, Drugbank and TTD databases. 3) 34 overlapping gene symbols related to CRC and drugs were obtained. 4) The results suggest that the anti-CRC components of D. officinale are mainly apigenin, naringenin, caffeic acid, γ-linolenic acid, α-linolenic acid, cis-10-heptadecenoic acid, etc., and the core targets of action are mainly ESR1, EGFR, PTGS2, MMP9, MMP2, PPARG, etc. 5) The proliferation of muscle cells, the regulation of inflammatory response, the response of cells to organic cyclic compounds, and the apoptotic signaling pathway might serve as principal pathways for CRC treatment. 6) The reliability of some important active ingredients and targets were further validated by molecular docking. The molecular docking analysis suggest an important role of apigenin, naringenin and PTGS2, MMP9 in delivering the pharmacological activity of D. officinale against CRC. 7)The results of evaluation experiment in vitro suggest that D. officinale has a strong inhibitory effect on CRC cell lines and it exerts anti-CRC activity by activating CRC cell apoptosis and inhibiting CRC cell migration, invasion. Conclusions: This study may provide valuable insights into exploring the mechanism of action of D. officinale against CRC.